Measurement of Urban Ecological Sustainability Level (Case Study: Region 1 of Tabriz Metropolitan) - dr.hassan mahmoodzadeh; mehdi herischiyan (جغرافیا و آمایش شهری منطقه‌ای, 2018)
In recent years the balanced relationship between human and nature has been disrupted by rapid urban development and unbridled and destructive actions by the overexploitation of urban resources, resulting in fragile and volatile urban environments. So the present study was conducted to investigate the urban ecological sustainability of Region 1, Tabriz  metropolis ​​ with  59 sustainability components  in four environmental, social, economic, and physical groups using the Structural Equation (SIM) and Fuzzy Multivariate Analysis, and weighted linear combination (WLC) in GIS environment. The present research is applied, from the perspective of nature, and descriptive-empirical, from that of method. A researcher-made questionnaire were used to gather required data. The reliability coefficient of the questionnaire (0.93) was evaluated using Cronbach's alpha. A sample of 382 residents of Region 1 in Tabriz metropolitan was randomly selected. Using Linear regression test in the SPSS software, latent indicators were ranked and using factor loadings test in the LISREL software, observed indicators were ranked and summarized according to the importance and effectiveness levels. The fuzzy logic model in the form of GIS was used to prepare the map of influencing indicators. The results of the data analysis  indicate that all parts of the Region1 of Tabriz metropolitan area have are not sustainable, so that the northern, middle, and southern and southeastern neighborhoods are at low, middle, and high levels of sustainability, respectively. Therefore, the influencing factors at these irregular levels of sustainability in Region 1 were prioritized. Accordingly, environmental, social, economic, and physical indicators with respectively 46.2%, 30.1%, 19.7%, and 4%, play role, in order of priority, in this unbalanced sustainability. Hence, strengthening the influencing indicators based on their priorities was emphasized by offering a number of recommendations.